Design of Track Transitions: Research Results Digest 79. (Research results digest (Transit Cooperative Research Program) ;, 2006)
"This digest summarizes the results of TCRP Project D-7/Task 15. The digest was prepared by the Transportation Technology Center, Inc. ... David Read and Dingqing Li served as principal authors."